Denotative and Connotative meaning in Among Us Look Alike meme - Baruno Anggada Prabu; Andang Saehu; Irdan Hildansyah (Institut Agama Islam Negeri Palopo, 2024)
Memes as an entertainment media have become a way to communicate with people of this era as a way to deliver a message or to retell the events of today or the past. The Among Us is one amongst many memes existed on the internet, once starting of as a small community exclusive to enthusiasts to something that ordinary people can enjoy whether it is from things that relate to them as of playing the game or something sensational that spreads into everyday objects, thus created subgenre “Among Us Look Alike”. The method chosen for this research is descriptive qualitative with an addition of parts needed to construct the meme. The researcher uses Roland Barthes’ theory to analyze the data. The researcher also explained the Denotative and Connotative meaning in the Among Us Look Alike meme. The researchers selected two memes for this analysis in Among Us memes based on the appearance of the Among Us character in the image. The result show that the Denotative meaning of the data are what to be expected from the object itself, and Connotative meaning of the data are varied and explained deeper into the context, such as the first data explaining the office culture and speculate on where the image is happening to how the image with the context presented to be in an office culture preceded the Among Us games by few months and the second data explaining the post-apocalyptic event and how the trace of Among Us character survived due to its material and how it shares the same material as the currency of the post-apocalyptic zone of “Fallout” game. The data showed that the images have both Denotative which is the literal description of the object and Connotative which range from just knowing the basic context of the meme, which is to know what parts needed to manifest the figure into deeper subjective meaning of the image.